Expresión de la integrina ?v?3 y de las subunidades de integrinas ?3 y ?1 durante la placentación porcina. - Williamson, D.M. (2009)
Porcine placenta is epitheliochorial, diffuse, folded, adecidua, and non invasive, and express adhesion molecules different. Integrins are glycoproteins composed of ? and ? subunits that govern cellular interactions with the extracellular matrix. Recent studies showed that integrins have been involved in implantation events in several species. The aim of this study was to compare the expression of ?v?3, ?3 and ?1 during placentation porcine. Placental tissue from porcine female of 37, 60, 70, 80 and 114 days of gestation, and empty uterus were used. The detection of the integrins was analyzed by indirect immunoperoxidase. During placentation avb3 was expressed abundantly, decreasing from day 80 on. The integrins ?1 was the one that marked great positivity in all placental tissues studied, decreasing it expression only at the end of de gestation. The ?3 subunits was not expressed in endometrials glands in none of the gestational periods studied. The results of this study remark the importance of the expression of integrins during the porcine placentation, particularly ?1, during the gestation to allow the redesigning of the placental villi and ?3 from interareolares zones.\n